Visualizing software a graphical nolation for analysis, design, and discussion - Bennet, William S (Marcel Dekker, 1992)
Introduces a graphical design representation for software, focusing on improving the reader's ability to simulate the behaviour of software mentality. This work explains how the new notation is useful in the primary documentation of software designs as well as in discussions and design reviews.